Pemanfaatan Kompos Daun Ketapang (Terminalia catappa) sebagai Amelioran Tanah Pasca Tambang untuk Budidaya Selada (Lactuca sativa L) - Amprin, Amprin; Dian , Triadiawarman; Veronika , Murtinah; Benny , Kurniawan; Dhani, Aryanto; Purwanti, Santi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Post-mining soils are commonly characterized by poor chemical properties that limit plant growth and agricultural productivity. This study aimed to evaluate the effectiveness of Ketapang (Terminalia catappa) leaf compost as an organic soil ameliorant for improving soil chemical properties and supporting lettuce cultivation on post-mining land. The experiment was conducted using several proportions of Ketapang leaf compost incorporated into post-mining soil as planting media. Observed parameters included soil chemical properties, namely soil pH, organic carbon, total nitrogen, and available phosphorus, as well as lettuce growth indicators such as plant height, leaf width, leaf number, and biomass. The results demonstrated that increasing the proportion of Ketapang leaf compost significantly enhanced soil organic carbon, total nitrogen, and available phosphorus contents. Soil pH also improved at higher compost application rates, indicating better chemical conditions for plant growth. Improvements in soil chemical properties were accompanied by enhanced lettuce growth performance, particularly in plant height, leaf width, and fresh biomass. The parameters of number of leaves and dry biomass did not show significant differences. Ketapang leaf compost has strong potential as a sustainable organic ameliorant for rehabilitating post-mining soils while supporting lettuce production. The utilization of locally available organic materials offers an environmentally friendly approach to land restoration and sustainable horticultural development.